The Description of Stress Level and Learning Saturation During Online Learning of Nursing Students - Indah Septiana Saputri; Etlidawati Etlidawati (Proceedings Series on Health & Medical Sciences, 2021)
The change in learning models from conventional to online during the Covid-19 pandemic is a solution so that the learning process continues. That can make students in a state of stress and boredom. To find a description of the level of stress and boredom of learning in online learning for Nursing students S1 Muhammadiyah University of Purwokerto. This research was descriptive quantitative using survey method. The number of samples were 148 respondents using the proportional stratified random sampling technique. The independent variables in this study were the level of stress and learning saturation. The questionnaire used in this study was a modified DASS-42. The data analysis used univariate analysis. The results showed that the stress levels of students in online learning were mostly in the medium category as many as 88 (59.4%), mild as much as 43 (29.1%), normal as much as 12 (8.1%), heavy as much as 5 ( 3,4%) and no one experienced stress in the very heavy category. Then the level of learning saturation is most dominant in the moderate category as many as 71 (48%), high as much as 40 (27%), low as much as 30 (20.3%), and very high as much as 7 (4.7%). The level of stress and boredom of learning in online learning for third semester undergraduate nursing students is in the medium category. From the results of the study, it is recommended that respondents are be able to anticipate the occurrence of stress and learning saturation by knowing the causes of stress and learning saturation